ANALISIS REAKSI PASAR MODAL SETELAH PENGUMUMAN INITIAL PUBLIC OFFERING (IPO) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA - Saint - Paulia Y.S; Armanu Thoyib; M. Syafiie - Idrus (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACT Stock exchange is a means to acquire capital and accumulate funds, therefore it is important in improving the public’s participation in generating fund so as to support the national development. The meaning of IPO is when the company issues its stocks for the first time in the stock exchange. Therefore an IPO will result in a number of reactions from the capital market, and one of such reactions is return. Purpose of this research was to investigate whether the performance of stock exchanges in Indonesia is decreasing in the long run and whether there exists a difference between short term stock performance and long term stock performance and also the performance of the securities bought in first day’s closing price. The survey method was used in this research. The research belong to deductive-quantitative by tested stock performance in short term and long term period of IPO up to one year. The abnormal return was calculated based on the total stock return, total market value, market adjusted model and relative wealth. The sample was constructed using purposive sampling technique from a population of 43 companies which conducted their IPO in the period from January 2002 up to December 2002 in Jakarta Stock Exchange. The statistic method used here was normality test, in which Kolmogorov-Smirnov Goodness-of-Fit test was first applied and then followed by difference test using one sample t-test and Wilcoxon matched-pair signed rank test. The result of this study showed that for the short term, the first day of trading resulted in positive mean of abnormal return, which turned into negative in the long period. This means that in the short term, the result is outperforming and in the long term the result is underperforming. For the stocks acquired with initial price, the short term and long term performance did not indicate any difference. However, for the stocks acquired with the first day’s closing price, the short term and long term performance for a period of one month was found to be different from the performance of one year. This shows that the significant difference occurred only for the fist day of trading. Keywords: abnormal return, stock performance